Spontaneous pneumothorax and pneumomediastinum after a trivial injury: a case report - Rakawi, Ahmad Faizal; Marwan, Abdul Aziz; Daut, Ummi Nadira (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2020)
Spontaneous pneumothorax and pneumomediastinum is defined as presence of free air or gas in the pleural cavity and mediastinal structures respectively. Spontaneous pneumothorax seems to be associated with anatomical abnormalities such as subpleural blebs or bullae, however not for spontaneous pneumomediastinum which may developed without an apparent precipitating cause. Both usually may occur in young healthy adults without serious underlying lung disease. We report a case of spontaneous pneumothorax and pneumomediastinum after a trivial injury. He was initially presented with dyspnea after two weeks of initial trivial trauma. Chest radiograph showed left apical pneumothorax with pneumomediastinum with no evidence of rib fracture. His condition was deemed non-traumatic by surgical colleague, thus admitted to medical ward for observation and eventually discharged well.